Perioperative and mid-term outcomes of robotic-assisted versus video-assisted minimally invasive esophagectomy for esophageal cancer: a retrospective propensity-matched analysis of 842 patients - Huang, Jiang-shan; Zhu, Jia-fu; Zhong, Qi-hong; Guo, Fei-long; Lin, Yu-kang; Zhang, Zhen-yang; Lin, Jiang-bo (Frontiers in Oncology, 2024)
Aim: Comparing the safety, effectiveness, and mid-term survival rates of robot-assisted minimally invasive esophagectomy (RAMIE) and video-assisted minimally invasive esophagectomy (VAMIE). Methods: A total of 842 patients undergoing minimally invasive esophagectomy were analyzed, including 694 patients in VAMIE group and 148 in RAMIE group. PSM analysis was applied to generate matched pairs for further comparison. Operative outcomes, postoperative complications and Mid-term outcomes were compared between all patients in matched groups. Results: After 1:4 PSM, 148 patients in the RAMIE and 592 patients in the VAMIE. Compared to VAMIE, RAMIE exhibited earlier removal of chest and neck drainage tubes, shorter postoperative hospital stays, and a higher number of lymph node dissections. However, the surgical duration of RAMIE was longer than that of VAMIE. Postoperative complications were no statistically significant between the RAMIE and VAMIE groups. There was no statistically significant difference in the 3-year OS and DFS between the two groups. Conclusion: Compared to VAMIE, RAMIE emerges as a viable and safe surgical approach and suggests RAMIE as a potential alternative to minimally invasive esophagectomy.